Ramosin: The First Antibacterial Peptide Identified on Bolitoglossa ramosi Colombian Salamander - Laura Medina; Fanny Guzmán; Claudio Álvarez; Jean Paul Delgado; Belfran Carbonell-M (Pharmaceutics, 2022)
The discovery and improvements of antimicrobial peptides (AMPs) have become an alternative to conventional antibiotics. They are usually small and heat-stable peptides, exhibiting inhibitory activity against Gram-negative and Gram-positive bacteria. In this way, studies on broad-spectrum AMPs found in amphibians with the remarkable capability to regenerate a wide array of tissues are of particular interest in the search for new strategies to treat multidrug-resistant bacterial strains. In this work, the use of bioinformatic approaches such as sequence alignment with Fasta36 and prediction of antimicrobial activity allowed the identification of the Ramosin peptide from the de novo assembled transcriptome of the plethodontid salamander Bolitoglossa ramosi obtained from post-amputation of the upper limb tissue, heart, and intestine samples. BLAST analysis revealed that the Ramosin peptide sequence is unique in Bolitoglossa ramosi. The peptide was chemically synthesized, and physicochemical properties were characterized. Furthermore, the in vitro antimicrobial activity against relevant Gram-positive and Gram-negative human pathogenic bacteria was demonstrated. Finally, no effect against eukaryotic cells or human red blood cells was evidenced. This is the first antibacterial peptide identified from a Colombian endemic salamander with interesting antimicrobial properties and no hemolytic activity.